Productivity Potential, Quality and Profitability of Sweet Corn (Zea mays var. saccharata) under Diverse Nitrogen Management Practices in Mid-hills of Meghalaya - Devi, K. Surjarani; Singh, A. K; Kumar, Rajesh (Indian Journal of Hill Farming, 2019)
A field experiment was conducted to find out suitable level and source of nitrogen (N) for sweet corn (Sugar 75) at experimental Farm, College of Post Graduate Studies (CAU, Imphal), Umiam, Meghalaya during the Kharif season of 2012. Results indicated that various nitrogen sources and level extended the significant effect on yield attributes, yield, quality and economic output of sweet corn. Variation in levels of N brought an increase in population, cob length, number of grains per cob, test weight, gross returns, net returns and B: C ratio was recorded with each increment in N levels up to 120 kg ha-1 . Though the difference between 80 and 120 kg ha-1 N for these parameters was at par but both these treatment recorded significantly high values over 40 kg N ha-1. Maximum cob yield (8.2 t ha-1) was observed from the treatment received nitrogen through poultry manure which was at par with FYM but produced significantly higher fresh cobs yield over compost and urea applied N sources. There was found no significant effect of levels and sources of N on harvest index. However, quality of sweet corn kernels did not differ either due to levels or source of N.